Cigarette smoking and cerebral blood flow in a cohort of middle-aged adults - Paulson, Olaf B (J Cereb Blood Flow Metab, 2020)
Cigarette smoking increases cerebral blood flow. Both nicotine and carbon monoxide contribute to the flow increase. Due to carbon monoxide’s high affinity to hemoglobin and slow clearance from the blood, the effect lasts for hours. Nicotine also stays in the organism for some hours. This immediate effect of smoking may explain a recently observed higher cerebral blood flow in current-smokers as compared to former-smokers.